Investigation of heat transfer enhancement by perforated helical twisted-tapes - Nanan, K.; Thianpong, C.; Promvonge, P.; Eiamsa-ard, S. (My University, 2014)
Influence of perforated helical twisted-tapes (P-HTTs) on the heat transfer, friction loss and thermal performance characteristics under a uniform heat flux condition is reported. The P-HTTs were obtained by perforating typical helical twisted-tapes (HTTs) with a prospect to reduce the friction loss of fluid flow. The experiments were conducted using P-HTTs' three different diameter ratios (d/. w) of 0.2, 0.4 and 0.6, and three different perforation pitch ratios (s/. w) of 1, 1.5 and 2. The helical pitch ratio and twist ratio were fixed at P/. D=2 and y/. w=3. Tests were performed for Reynolds number between 6000 and 20,000. The experiments using the plain tube and the tubes with HTTs were also carried out for assessment. The experimental results reveal that the use of P-HTTs leads to the reduction of friction loss as compare to that of HTT. Heat transfer, friction loss and thermal performance factor increase as d/. w decreases and s/. w increases. For the present range, the maximum thermal performance factor of 1.28 is obtained by using the P-HTT with d/. w=0.2 and s/. w=2.0 at the Reynolds number of 6000. In addition, the empirical correlations for Nusselt number, friction factor and thermal performance factor give accurate predictions within ±. 4%, ±. 6% and ±. 3%, respectively. © 2014 Elsevier Ltd.
Keywords: Heat transfer; Perforated helical twisted tapes; Pressure loss; Thermal performance